2022
DOI: 10.5530/ijper.56.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective Potential of Stem Bark of Neolamarckia cadamba against Chloroform and Over dose of Iron Dextran Induced Hepatotoxicity in Experimental Swiss Albino Mice

Abstract: Background:In general, use of herbal medicines are considered as the backbone in traditional system of medicines as it has been used for food, flavoring agents and in the form of medicines. Keeping in knowledge the increasing demand of herbal drugs over their synthetic counter parts and to restrain the worldwide problem of multidrug resistance (MDR) in hepatoprotective activity. Neolamarckia cadamba that is commonly called Cadamb is a standout amongst the most significant therapeutic plants having a place with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Rachsee et al, 100 107 observed that oral administration of stem bark of ethanolic extract of 0.5 g/kg body weight exhibited a significantly reduced hyperglycemia in alloxan-induced diabetic rats. Das et al, 108 tested the hepatoprotective activity of hydroalcoholic extract of N.cadamba stem bark in Swiss albino mice using chloroform and iron overdose hepatotoxicity. The research demonstrated N.cadamba's hepatoprotective effect in both hepatotoxicity models, and the activity is probably due to its potent antioxidant and iron-chelating properties.…”
Section: Mucuna Pruriens Lmentioning
confidence: 99%
“…Rachsee et al, 100 107 observed that oral administration of stem bark of ethanolic extract of 0.5 g/kg body weight exhibited a significantly reduced hyperglycemia in alloxan-induced diabetic rats. Das et al, 108 tested the hepatoprotective activity of hydroalcoholic extract of N.cadamba stem bark in Swiss albino mice using chloroform and iron overdose hepatotoxicity. The research demonstrated N.cadamba's hepatoprotective effect in both hepatotoxicity models, and the activity is probably due to its potent antioxidant and iron-chelating properties.…”
Section: Mucuna Pruriens Lmentioning
confidence: 99%